2005
DOI: 10.1055/s-2005-837737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nuchal Cord on Birthweight and Immediate Neonatal Outcomes

Abstract: Our objective was to ascertain if nuchal cord is associated with adverse neonatal outcomes. Using a retrospective database of term neonates, outcomes were compared among infants with 0, 1, and 2 or more loops of cord encircling the neck. Of 4426 neonates, 3651 served as controls, 691 had one loop, and 84 had two or more loops. There were no significant differences in the mean birthweight, the frequency of nonreassuring fetal heart rate patterns, operative vaginal deliveries, or 5-minute Apgar scores of < 7. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
1
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 9 publications
7
33
1
3
Order By: Relevance
“…9,10 When the intra partum events were monitored, it was found that FHR irregularities were more common in control group 55/115 (47.8%) than in the study group 18/50 (36%) but statistically not significant. This finding correlates with that of Mastbattisia 11 and Carey et al 12 , who found statistically no difference b/w the two groups, where as Sheiner et al 13 observed an increased rate of non-reassuring FHR pattern in the nuchal cord group.…”
Section: Discussionsupporting
confidence: 85%
“…9,10 When the intra partum events were monitored, it was found that FHR irregularities were more common in control group 55/115 (47.8%) than in the study group 18/50 (36%) but statistically not significant. This finding correlates with that of Mastbattisia 11 and Carey et al 12 , who found statistically no difference b/w the two groups, where as Sheiner et al 13 observed an increased rate of non-reassuring FHR pattern in the nuchal cord group.…”
Section: Discussionsupporting
confidence: 85%
“…Several epidemiologic studies have noted that placental abruption complicates approximately 1% of adverse perinatal outcomes that were associated with the finding of NC on the NTS. Similar to published reports [2][3][4] regarding nuchal cords detected in the second and third trimester, we found no significant differences in the two groups with respect to birth weight, mode of delivery, placental insufficiency or abnormal umbilical artery Doppler. However, the prevalence of these conditions was lower than expected, and the study was underpowered to detect the actual level of difference deliveries, which is close to the percentage reported in our study [13].…”
Section: Discussionsupporting
confidence: 80%
“…There remains the question of clinical relevance of nuchal cords noted by sonography in the second or third trimesters and if there are any significant, subsequent perinatal adverse outcomes. Several studies have reported on the presence of nuchal cords at delivery; however, there is disagreement in the literature whether there is any impact on birth weight, abnormal intrapartum fetal heart rate tracings, cord gases, Apgar scores and mode of delivery [2][3][4]. Whether to search for their presence, and then to report their existence on the sonogram report, is still debatable and is imaging-center dependent [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…2,4,[14][15][16] On the other hand Mastrobattista JM et al stated that nuchal cord loops are not associated with increased foetal heart rate irregularities. 17 Electronic foetal monitoring may be the reason for detecting more number of fetal heart irregularities in our study. Although Larson et al stated that multiple nuchal loops are associated with abnormal foetal heart rate pattern.…”
Section: Discussionmentioning
confidence: 92%